A Recent Update on Advanced Molecular Diagnostic Techniques for COVID-19 Pandemic: An Overview - Roberts, Akanksha; Chouhan, Raghuraj Singh; Shahdeo, Deepshikha; Shrikrishna, Narlawar Sagar; Kesarwani, Veerbhan; Horvat, Milena; Gandhi, Sonu (Frontiers in Immunology, 2021)
Coronavirus disease 2019 (COVID-19), which started out as an outbreak of pneumonia, has now turned into a global pandemic due to its rapid transmission. Besides developing a vaccine, rapid, accurate, and cost-effective diagnosis is essential for monitoring and combating the spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its related variants on time with precision and accuracy. Currently, the gold standard for detection of SARS-CoV-2 is Reverse Transcription Polymerase Chain Reaction (RT-PCR), but it lacks accuracy, is time consuming, cumbersome and fails to detect multi-variant forms of the virus. Herein, we have summarized conventional diagnostic methods such as Chest-CT (Computed Tomography), RT-PCR, Loop Mediated Isothermal Amplification (LAMP), Reverse Transcription-LAMP (RT-LAMP), as well new modern diagnostics such as CRISPR–Cas based assays, Surface Enhanced Raman Spectroscopy (SERS), Lateral Flow Assays (LFA), Graphene-Field Effect Transistor (GraFET), electrochemical sensors, immunosensors, antisense oligonucleotides (ASOs) based assays, and microarrays for SARS-CoV-2 detection. This review will also provide an insight into an ongoing research and the possibility of developing more economical tools to tackle the COVID-19 pandemic.